Coat of many colours—DNA reveals polymorphism of mantle patterns and colouration in Caribbean Cyphoma Röding, 1798 (Gastropoda, Ovulidae) - Reijnen, B; Van Der Meij, S (PeerJ, 2017)
The iconic gastropod genus Cyphoma is commonly observed in the Caribbean, where it lives in association with various octocorallian hosts. Each species in the genus Cyphoma has a unique, characteristic mantle pattern and colouration, which separates the valid taxa. Because of its abundance and recognisability Cyphoma gibbosum has been used as a model organism in several studies concerning allelochemicals, reef degradation, and physical defence mechanisms. Molecular analyses based on four molecular markers (COI, 16S, H3 and 28S) for three Cyphoma species (C. gibbosum, C. mcgintyi, C. signatum) and an unidentified black morph, collected from three localities in the Caribbean, show that they represent morphological varieties of a single, genetically homogeneous species. This outcome is in agreement with previous anatomical studies. As a result C. mcgintyi and C. signatum are synonymised with C. gibbosum, which is a key result for future work using C. gibbosum as a model organism. The striking morphological differences in mantle pattern and colouration are hypothesised to be the result of one of three possible scenarios: rapid divergence, supergenes (including balanced polymorphism), or incipient speciation.